Kajian Hukum Terhadap Klausula Baku Non-Refundable Dalam Perjanjian Pemesanan Hotel Online - Suwandy, Davita Maisinda; Safrawa, Debby; Maretha, Dina Rizki (Media Hukum Indonesia (MHI), 2025)
The digitalization of the tourism industry through Online Travel Agent (OTA) platforms has led to the widespread use of non-refundable standard clauses in hotel bookings, in which consumer payments cannot be returned in the event of cancellation. These clauses raise legal concerns because they are unilateral in nature and potentially violate the principle of contractual balance. This normative (doctrinal) legal research aims to analyze the pattern of applying non-refundable clauses that are considered detrimental to consumers and to assess their compliance with the principles of transparency and clear information as regulated in Law Number 8 of 1999 on Consumer Protection (UUPK). The results and discussion show that non-refundable clauses are often applied rigidly and absolutely, even in cases of cancellations caused by system errors or force majeure, which substantively reduces consumer rights and potentially conflicts with Article 18 of the UUPK. In addition, the presentation of non-refundable information that is not prominent or is vague on digital platforms leads to consumer consent that is not based on full awareness, violating consumers’ rights to accurate, clear, and honest information (Articles 4 and 7 of the UUPK). It is concluded that the validity of such clauses highly depends on the transparency of information and the good faith of business actors. There is a need for regulatory reinforcement and industry standards that guarantee consumers’ rights to obtain fair refunds under certain conditions.